P5CS expression study in a new family with ALDH18A1‐associated hereditary spastic paraplegia SPG9. Issue 8 (19th July 2019) - Magini, Pamela; Marco‐Marin, Clara; Escamilla‐Honrubia, Juan M.; Martinelli, Diego; Dionisi-Vici, Carlo; Faravelli, Francesca; Forzano, Francesca; Seri, Marco; Rubio, Vicente; Panza, Emanuele
Abstract: In 2015–2016, we and others reported ALDH18A1 mutations causing dominant (SPG9A) or recessive (SPG9B) spastic paraplegia. In vitro production of the ALDH18A1 product, Δ 1 ‐pyrroline‐5‐carboxylate synthetase (P5CS), appeared necessary for cracking SPG9 disease‐causing mechanisms. We now describe a baculovirus–insect cell system that yields mgs of pure human P5CS and that has proven highly valuable with two novel P5CS mutations reported here in new SPG9B patients. We conclude that both mutations are disease‐causing, that SPG9B associates with partial P5CS deficiency and that it is clinically more severe than SPG9A, as reflected in onset age, disability, cognitive status, growth, and dysmorphic traits.